1998
DOI: 10.2307/3579883
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neutron-Induced Damage in DNA by Atomic Force Microscopy: Experimental Evidence of Clustered DNA Lesions

Abstract: Using atomic force microscopy (AFM), we have investigated neutron-induced DNA double-strand breaks in plasmids in aqueous solution. AFM permits direct measurement of individual DNA molecules with an accuracy of a few nanometers. Furthermore, the analysis of the DNA fragment size distribution is non-parametric, whereas other methods are dependent on the model. Neutron irradiation of DNA results in the generation of many short fragments, an observation not made for damage induced by low-LET radiation. These data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 30 publications
5
50
0
Order By: Relevance
“…What is more, the results in Figure 3 show a behavior qualitatively like that of a system with damped oscillations, characteristic of a fully homogeneous system. Very similar behavior observed for the results shown in Figure 4 was obtained by Pang and collaborators for distribution functions of fragment size using neutrons and electrons [21]. The curves shown were obtained by a simple fitting of power laws where it was found that the exponents are fractional.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…What is more, the results in Figure 3 show a behavior qualitatively like that of a system with damped oscillations, characteristic of a fully homogeneous system. Very similar behavior observed for the results shown in Figure 4 was obtained by Pang and collaborators for distribution functions of fragment size using neutrons and electrons [21]. The curves shown were obtained by a simple fitting of power laws where it was found that the exponents are fractional.…”
Section: Resultssupporting
confidence: 63%
“…Radiobiological research uses this powerful AFM imaging capability [13]. In fact, the investigation of DSBs induced by X-rays, neutrons, electrons, and alpha particles in plasmid DNA has been performed with AFM [14][15][16]. Results on damage induced in plasmid DNA by heavy ions have also been reported elsewhere [17].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, the ring-shaped plasmid will open and change to linear form if one double strand break takes place and more DSBs will fragment the plasmid to linear segments of shorter lengths. All these topological/lengths transformation of DNA are easy to resolve and quantify by gel electrophoresis [22][23][24] and AFM 7,8,[25][26][27][28][29] . However, it is very important to know that some structural changes may occur in intact supercoiled DNA upon the binding of plasmids to the mica surface.…”
Section: Analyzing Dna Structure Quantitatively At a Single-molecule mentioning
confidence: 99%
“…Conformation alterations of cruciforms can affect the binding of other proteins and may potentially facilitate the unwinding of the DNA duplex for transcriptional or replication processes. Our laboratories have used AFM imaging to investigate proteins, such as Ku, PARP-1, and apoptotic fragments of PARP-1, that bind to breaks of DNA after radiation exposure (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%